Regulation of hepatic nuclear guanylate cyclase. - Earp, H S (1977)
In immunohistochemical studies of rat liver tissue slices and purified nuclei, adenosine 3':5'-cyclic monophosphate (cAMP) and guanosine 3':5'-cyclic monophosphate (cGMP) immunofluorescence on the nuclear membrane are sequentially increased after glucagon administration. An explanation for the increased cGMP immunofluorescence was sought in experiments in which guanylate cyclase [GTP pyrophosphate-lyase (cyclizing), EC 4.6.1.2]activity of hepatic subcellular fractions was determined. The results showed that a nuclear guanylate cyclase exists which can be distinguished from the soluble and crude particulate guanylate cyclases. The activity of the nuclear enzyme was increased by 35% in nuclei isolated from rats 30 min after glucagon injection, the time at which maximal nuclear membrane cGMP immunofluorescence is observed. Because glucagon altered both cAMP location and levels prior to the observed changes in nuclear cGMP metabolism, the hypothesis that cAMP acted as the second messenger was tested. In vitro incubation of nuclei isolated from control rats with 10(-5) M cAMP produced a 25% increase in nuclear guanylate cyclase activity. With nuclei isolated from glucagon-treated rats, no significant increase in enzyme activity was observed; this indicates that maximal stimulation of nuclear guanylate cyclase by cAMP occurred at levels that are obtained in vivo after glucagon administration. These findings suggest that hepatic nuclear cGMP content may be regulated by a specific organelle guanylate cyclase and that cAMP may be one of the determinants of this enzyme's activity.